The Challenges of Law on the Edge of Social Chaos - Simonyan, Taron (Bulletin of Yerevan University C: Jurisprudence, 2022)
An attempt has been made in the article to answer three questions that are closely related to the challenges the law faces on the edge of social chaos:• What happens to the law when the dynamics of social change accelerate so much that the general purpose and meaning of coexistence is disturbed, lost or transformed, eliminating the points and directions of social gravitation?• What happens to law when the constituent factors of law (g., freedom, equality, justice) undergo semantic changes much faster than the public consciousness is able to digest, accept those changes as necessary means or value of organizing and directing its own life?• What happens to the law when the process of positivization of law in the conditions of accelerating social changes is largely conditioned not by the discovery of the law and the equilibrium of private and public interests, but by the factors of political expediency?
Keywords: social chaos; edge of chaos; uncertainty; complexity; social change; change of value bases of law; legal perception; legal consciousness